2019
DOI: 10.1016/j.surfcoat.2019.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure, mechanical and tribological properties of vanadium carbonitride coatings sputtered at different nitrogen partial pressures

Abstract: Vanadium carbide coatings were deposited by R.F. reactive magnetron sputtering at different nitrogen partial pressures. The structures and the mechanical and tribological behaviour of these coatings were studied. By using a combined approach of EDS and WDS, it has been shown that increasing nitrogen concentration from 0 to 27 at.% led to decrease the carbon content from 48.50 to 30.50 at.%. All coatings exhibited a dominant fcc-VC structure with additional fractions of vanadium nitrides, as determined by XRD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
(105 reference statements)
1
20
0
Order By: Relevance
“…The residual stresses generated in the films during the deposition procedure were calculated using the curvature method (Stoney's formula (Eq. 4)) [3]. The substrate-curvature radii before and after film deposition were measured with an optical profilometer (VEECO, Wyko-NT 1100).…”
Section: Characterization Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…The residual stresses generated in the films during the deposition procedure were calculated using the curvature method (Stoney's formula (Eq. 4)) [3]. The substrate-curvature radii before and after film deposition were measured with an optical profilometer (VEECO, Wyko-NT 1100).…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Where E s (181 GPa) and ν s (0.28) are the Young's modulus and Poisson's ratio of an iron substrate, respectively. t s and t f are the thicknesses of the substrate and the deposited film, respectively, while R 0 and R are the curvature radius before and after deposition, respectively [3]. The tribological behavior (friction coefficient) of the films was evaluated by sliding wear tests using a tribometer (CSM Instruments) under a ball-on-disc configuration.…”
Section: Characterization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Krause et al have reported the microstructure-property relationship of reactive magnetron sputtered VeN films deposited at different deposition angles [17]. In our recent study, we evaluated the influence of nitrogen partial pressure on the microstructure and mechanical and tribological behavior of V-C-N coatings [18]. Qiu et al have investigated the effect of nitrogen pressure and negative substrate bias on the microstructure and the mechanical performance of VeN films [19].…”
mentioning
confidence: 96%
“…Lee etc [15] deposited 30 nm-thick InZnSnO film transistors with RF magnetron sputtering with various oxygen partial pressures, and found that the oxygen partial pressure affected the overall electrical properties of the thin film transistors, which was associated with the change of interface trap density. Zgheib etc [16] deposited vanadium carbide coatings with RF reactive magnetron sputtering at different nitrogen partial pressures. They found that the increase of nitrogen concentration from 0 to 27 at.…”
Section: Introductionmentioning
confidence: 99%